Shipwrecks and provenance : in-situ timber sampling protocols with a focus on wrecks of the Iberian shipbuilding tradition - Rich, Sara A., (Archaeopress Publishing Ltd, 2018)
This work presents a set of protocols to establish the need for wood samples from shipwrecks and to guide archaeologists in the removal of samples for a suite of archaeometric techniques currently available to provenance the timbers used to construct wooden ships and boats. Case studies presented use Iberian ships of the 16th to 18th centuries.